Analisis Spasial Kasus Leptospirosis di Perbatasan Kabupaten Bantul, Sleman, dan Kulon Progo - Nurbeti, Maftuhah; Kusnanto, Hari; Nugroho, Widagdo Sri (Kes Mas: Jurnal Fakultas Kesehatan Masyarakat, 2016)
Background: Leptospirosis is an important issue in Yogyakarta Province. Outbreak status had set in Sleman, Bantul, and Kulonprogo District. The border areas have the most cases. This study aimed to analyze: cluster based on the buffer of distance from case’s home to rice fields, rivers, and roads; as well as observed patterns of disease diffusion and frequency over time. Method: This study was an observational study. There were 327 subjects obtained from all cases of Leptospirosis who were reported in District Health Office from 2009-2011. They were living in seven sub-districts, namely Sedayu, Minggir, Moyudan, Godean, Sentolo, Nanggulan, and Kalibawang. Results: 1) Most of the cases were distributed in the agricultural area, area drained by many river streams, and area with moderate rainfall (2000-2500 mm/year). There was no specific distribution pattern in overlay of cases map with maps of population density, density of poor households, altitude, and density of livestock. 2) Buffer analysis showed a cluster based on the distance between cases home with rice fields, rivers, and roads. 3) All cases in the seven sub-district was one unit cluster. The area is the most widely drained by large and small rivers. Cluster scores are higher in areas with the highest deprivation scores and has the most widely watershed. We found some Leptospirosis clusters which were across-district, across sub districts, and across the river. 4) Disease diffusion of Leptospirosis cases was an infectious type of expansion diffusion. There was a seasonal pattern according to the planting season and the beginning of the rainy season. There was a trend of increase in Leptospirosis cases from year to year. Conclusion: Leptospirosis disease in the border of Bantul, Sleman, and Kulonprogo District did not spread through the river from one region to another, but very much related to the watershed.